IMPACT OF RAFTING ON THE CIMANUK RIVER IN SUMEDANG ON LOCAL ECONOMY - M. Rahman Fitriansyah; Dinar Dinangsit; Rizal Ahmad Fauzi (UNIVERSITAS NEGERI JAKARTA POSTGRADUATE OF PHYSICAL EDUCATION DEPARTMENTS, 2025)
The development of tourism in Indonesia is currently quite advanced. According to the WTTC Travel and Tourism Power and Performance, Indonesia ranks 9th out of 30 countries, surpassing several developed countries such as Malaysia, Thailand, the United Arab Emirates, and Australia. However, each tourist destination generally has its own impact on the local community, whether positive or negative. Therefore, this research aims to determine the impact caused by the presence of white-water rafting tourism on the Cimanuk River in Parakan Kondang on the local economy. The method used in this research is a qualitative method with a descriptive design, conducted at the Cimanuk River in Parakan Kondang, Sumedang Regency. The subjects of this study are the head of DISPARBUDPORA Sumedang Regency, rafting operators, and 9 affected business owners. The research instruments used are observation, interviews, and documentation. Data analysis was conducted using the Nvivo12 software application, and the results showed that white-water rafting significantly helps the local economy and opens up new business opportunities, thereby benefiting many members of the community through the presence of white-water rafting tourism. Thus, it can be concluded that white-water rafting on the Cimanuk River in Parakan Kondang, Sumedang Regency, has a positive impact on the local economy.